LAYANAN BIMBINGAN KLASIKAL SECARA ONLINE DALAM MENGATASI KEJENUHAN BELAJAR SELAMA PANDEMI COVID-19 - Aldila Fitri Radite Nur Maynawati; Monika Ayu Nurhayati; Yuraida Ita Kurniawati (JCOSE Jurnal Bimbingan dan Konseling, 2022)
This research is motivated by the existence of students who experience boredom in learning. This study aims to describe the boredom of learning through classical guidance services for students at SMA Negeri 3 Sukoharjo. The process of providing services is provided to students online by complying with government policies during the COVID-19 pandemic. However, in the implementation of learning, there are many obstacles, ranging from signal problems, to internet quotas that occur in the online learning process. However, not all students experience these obstacles, there are students who can follow the learning process from to completion. This study is intended to determine learning saturation, to how to overcome learning boredom in students. The research method used in this research is qualitative case handling in order to help overcome the boredom of learning in students at SMA Negeri 3 Sukoharjo. The results of this study show that students experience learning saturation due to emotional exhaustion that occurs repeatedly over a long period of time.